'In the Absence of Originals': Replicating the Tilework of Safavid Isfahan for South Kensington. (1st July 2014) - Carey, Moya
In 1877, Robert Murdoch Smith, the Victoria and Albert Museum's agent in Iran, undertook a brief project that differed from his more typical modus of bulk purchasing from local dealers and private collectors. Unable to purchase original decorative tilework from Safavid Isfahan's sacred monuments, he commissioned flat, full-size copies of 33 designs, traced directly from the tiled surfaces of six building complexes, and painted in full colour. Thus the South Kensington Museum (as it then was) would possess a record of these historic surface designs, and not the glazed tiles themselves. As such they still satisfied the Museum's mission to inform and improve contemporary practice in British industry. The primary site was the Madrasa-ye Madar-e Shah complex on Chahar Bagh Avenue, a prominent monument close to Murdoch Smith's offices in Isfahan. Since the seventeenth and early eighteenth centuries, the madrasa and two other major Safavid mosques had been recorded and illustrated by European visitors, and published by these outsiders as national epitomes. The 1877 project marks a waystage in this increasingly international visibility, occurring long after these monuments were first built as Safavid projections of splendour, and not long before their cosmetic appearance acquired renewed political significance in Pahlavi Iran.